The Job Performance of Emergency Nurses and its Relationship with Spiritual Intelligence and Occupational Hardiness - Fahimeh Dehghani; Fatemeh Foroughian Yazdi; Rohollah Askari (Golestan University of Medical Sciences, 2019)
Background: The quality of hospital systems depends greatly on the performance of nurses, and the performance of nurses has a significant effect on individual patients` satisfaction. Therefore, it is important to examine the factors related to nurses' performance. This study was designed to investigate the relationship between spiritual intelligence and occupational hardiness and the job performance in pre-hospital and hospital emergency nurses in Yazd. Methods: This cross-sectional study was carried out on 132 nurses working in pre-hospital and hospital emergency in Yazd University of Medical Sciences, who were selected using stratified sampling with proportional allocation in 2016. Data were collected through three questionnaires including spiritual intelligence, occupational hardiness and job performance. Data was analyzed using descriptive statistics and multiple regression in SPSS version 19.0 (IBM, USA). Results: The mean score of job performance, spiritual intelligence and occupational hardiness were 52.46±11.16, 121.32±12.59, and 53.29±8.72, respectively. According to the results, spiritual intelligence and occupational hardiness can predict the job performance. (R2=%18, P<0.01). Both spiritual intelligence (β=0.32, P=0.001) and occupational hardiness (β=0.24, P=0.004) showed significant positive contribution in the prediction of the job performance. Conclusions: According to the results, developing spiritual intelligence and occupational hardiness can help to improve the job performance of the pre-hospital and hospital emergency nurses.